Concentration of soil-transmitted helminth eggs in sludge from South Africa and Senegal: A probabilistic estimation of infection risks associated with agricultural application. (15th January 2018) - Amoah, Isaac Dennis; Reddy, Poovendhree; Seidu, Razak; Stenström, Thor Axel
Abstract: The use of sludge in agriculture has been encouraged as a means of increasing soil nutrient content and improving the water holding capacity. On the negative side, major public health concerns with sludge application prevail, mainly due to the high concentration of pathogenic microorganisms. Soil-transmitted helminths (STHs) are of major health concern in this regard, especially in endemic regions, mainly due to the high environmental resistant of the eggs combined with a low infectious dose. In this study the concentration of STH eggs in two months dried sludge from Durban, South Africa and Dakar, Senegal was determined and compared. Sampling was carried out from January to October 2016 and in September 2016 for Dakar. Ascaris spp, hookworm, Trichuris spp, Taenia spp and Toxocara spp were the commonly recorded STH eggs. STH egg concentrations were higher in Dakar than in Durban, with viable STH egg concentrations exceeding both local and international guidelines. Due to the high concentration of viable STH eggs, risks of Ascaris spp infection was very high for farmers applying this sludge on their farms in both Durban (7.9 × 10 −1 (±1.7 × 10 −2 )) and Dakar (9.9 × 10 −1 (±1.3 × 10 −5 )). Consumption of lettuce grown on sludge amended soil will result in probable infections but harvest after 30 days between sludge application and harvest in Durban gave median probability infection risks with a risk level similar to the WHO tolerable risk value (10 −4 ). This time period need to be prolonged to harvest in Dakar to 40 days to reduce the risks of infection to the tolerable risks values. Further treatment of the sludge either through composting or drying for longer periods of time is thus recommended from a public health perspective. Highlights: Sludge contained high concentration of viable STH eggs after 60 days of drying. The concentration of these eggs exceeded both national and international guidelines for reuse. Farmers and consumers of the farm produce are likely to be infected with Ascaris spp. Further treatment of the sludge is thus recommended from a public health perspective.